The Efficiency and Evolution of R&D Networks - Michael D. König; S. Battiston; M. Napoletano; F. Schweitzer (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
This work introduces a new model to investigate the efficiency and evolution of networks of firms exchanging knowledge in R&D partnerships. We first examine the efficiency of a given network structure in terms of the maximization of total profits in the industry. We show that the efficient network structure depends on the marginal cost of collaboration. When the marginal cost is low, the complete graph is efficient. However, a high marginal cost implies that the efficient network is sparser and has a core-periphery structure. Next, we examine the evolution of the network struc- ture when the decision on collaborating partners is decentralized. We show the existence of mul- tiple equilibrium structures which are in general inefficient. This is due to (i) the path dependent character of the partner selection process, (ii) the presence of knowledge externalities and (iii) the presence of severance costs involved in link deletion. Finally, we study the properties of the emerg- ing equilibrium networks and we show that they are coherent with the stylized facts of R&D net- works.
Keywords: D85; L24; O33; 330; R&D networks; technology spillovers; network efficiency; network formation; Industrieforschung; Unternehmensnetzwerk; Organisationsstruktur; Spillover-Effekt; Graphentheorie; Theorie